Effect of a computerized decision support system on the treatment approach of stage III or IV pressure injury in patients with spinal cord injury: a feasibility study - Anke Scheel-Sailer; Kamran Koligi; Patricia Lampart; Carina Fähndrich; Hans Peter Gmünder; Stefan Metzger; Dirk Schaefer; Klaus Schmitt; Stefan Stalder; Reto Wettstein; Armin Gemperli (BMC, 2023)
Abstract Background Stage III and IV pressure injuries (PIs) in patients with spinal cord injury (SCI) require complex interdisciplinary and interprofessional treatment approaches that are difficult to implement. Practical aspects, such as information exchange and coordination, remain challenging. We investigated whether a computerized decision support system (CDSS) could increase treatment adherence and improve clinical outcomes and interprofessional collaboration. Method In this feasibility study, a core team developed the initial treatment process and adapted it based on several discussions with clinical experts and information technologists. The CDSS followed the Basel Decubitus Approach and was used in a clinic specializing in SCI. Thirty patients with SCI admitted for stage III/IV PI between July 2016 and May 2017 were randomly allocated to standard or CDSS-supported care. Between-group differences in treatment adherence, complication rates, length of stay, and costs were analyzed using descriptive statistics. The use of the CDSS and potential barriers and facilitators were evaluated through interprofessional focus groups, transcribed verbatim, and thematically analyzed (30 participants). Results No differences in SCI characteristics, comorbidities, or PI characteristics (localization: ischium [number (n) = 19 PI, 63%], sacrum [n = 10 PI, 33%], recurrent PI [n = 21, 70%]) were found between the two groups. Furthermore, no statistically significant differences were observed in treatment adherence, frequency of major (20% vs. 13% between CDSS and control group) and minor (33% vs 27%) complications, and length of stay (98 [±28] vs 81 [±23] days). Healthcare professionals found the CDSS to be helpful for visualizing the treatment process. However, the high workload and difficulties in the information technology processes, such as missing reminders, slow computer performance and data processing, and poor accessibility, hindered the effective implementation of the CDSS. Conclusion The implementation of the CDSS to support the treatment of stage III/IV PI in patients with SCI was feasible and included definitions of milestones, interventions, and outcomes. However, to assess the impact of the CDSS, a longer observation period is required. Further, the technical difficulties must be addressed, and solid integration of the CDSS into the clinical information system is necessary. Trial Registration This quality improvement project received a declaration of no objection from the Ethics Committee of Northwest and Central Switzerland (EKNZ UBE-16/003), and ethical approval was received for the focus groups (EKNZ Req-2017-00860).